Multinationals, Robots, and the Labor Share - Fabrizio Leone (CESifo GmbH, 2024)
Using a panel of Spanish manufacturing firms covering the 1990-2017 period, I document new evidence about affiliates of multinational enterprises (MNEs): after being acquired, they exhibit a higher propensity to use robots, which leads to a reduction in their labor share. These effects are identified using a matched event-study design, which accounts for selection into multinational ownership and robot adoption. The findings are consistent with a model of robot adoption choices by heterogeneous firms and hold even after considering other explanations for the labor share decline. The estimates imply that without MNEs, the reduction in the manufacturing labor share over the sample period would have been 8% smaller. Multinational-induced robot adoption explains about one-third of the overall impact of multinational activity on the labor share.
Keywords: F23; F66; O33; 330; multinational enterprises; globalization; robots; labor share